Empirical Study of Employment Arrangements and Precariousness in Australia - Louie, Amber; Ostry, Aleck; Quinlan, Michael; Keegel, Tessa; Shoveller, Jean; LaMontagne, Anthony (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2006)
Much research on precarious employment compares permanent workers with one or two other broadly-defined employment categories. We developed a more refined method of examining precariousness by defining current employment arrangements in terms of job characteristics. These employment arrangement categories were then compared in terms of socio-demographics and self-reported job insecurity. This investigation was based on a cross-sectional population-based survey of a random sample of 1,101 working Australians. Eight mutually exclusive employment categories were identified: Permanent Full-time (46.4%), Permanent Part-time (18.3%), Casual Full-time (2.7%), Casual Part-time (9.3%), Fixed Term Contract (2.1%), Labour Hire (3.6%), Own Account Self-employed (7.4%), and Other Self-employed (9.5%). These showed significant and coherent differences in job characteristics, socio-demographics and perceived job insecurity. These empirically-supported categories may provide a conceptual guide for government agencies, policy makers and researchers in areas including occupational health and safety, taxation, labour market regulations, the working poor, child poverty, benefit programs, industrial relations, and skills development.